The Relationship between Organizational Self-Esteem, Commitment, Tipping and Organizational Citizenship Behaviors: A Case in the Foodservice Industry - Jamroch, Grayson; Barreda, Albert A; Kageyama, Yoshimasa (Journal of Tourism Management Research, 2020)
Given the limited research on Organizational Citizenship Behavior in the foodservice industry, this study attempts to investigate the effect of organizational self-esteem, organizational commitment, and the reception of tipping on organizational citizenship behavior. This study provides the necessary context to the relative mindset of the selected study participants (working students of Hospitality within restaurant organizations). Using the analysis of 45 tested (surveyed) students within a university setting; this study successfully drew conclusions about the relative correlation between the aforementioned constructs. The findings of the study contribute to the literature by helping and guiding foodservice and hospitality practitioners to consider influencing the perception of reception of tipping, the development of organizational self-esteem, and the positive organizational commitment to ensure that organizational citizen behavior is built. This paper can be useful for educators, managers, researchers, and students who are attempting to provide context for the contributions towards a positive working environment, and the implications of such.